2022
DOI: 10.1016/j.nut.2021.111512
|View full text |Cite
|
Sign up to set email alerts
|

Enteral nutritional support for patients hospitalized with COVID-19: Results from the first wave in a public hospital

Abstract: Background & aims Nutrition has become an important component in treating individuals during the COVID-19 pandemic, which is increasingly affecting the world population, and bringing with it a collapse in health services. Prolonged hospitalization, involving immobilization and catabolism, induces a decrease in body weight and muscle mass that may result in sarcopenia, a condition that impairs respiratory and cardiac function, worsening the prognosis. The present study aimed to analyze enteral nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 29 publications
0
18
0
5
Order By: Relevance
“…Seven studies were included in the systematic review, and four studies were used for the meta-analysis ( Figure 1 ). Three studies were conducted in the US [ 24 , 25 , 26 ], and there was one study each from Brazil [ 27 ], Greece [ 28 ], Mexico [ 7 ] and China [ 29 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies were included in the systematic review, and four studies were used for the meta-analysis ( Figure 1 ). Three studies were conducted in the US [ 24 , 25 , 26 ], and there was one study each from Brazil [ 27 ], Greece [ 28 ], Mexico [ 7 ] and China [ 29 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [ 24 , 27 ] showed an unclear risk of bias in relation to missing data, one study was with respect to the selection of participants [ 7 ], and another study was in relation to confounding variables [ 25 ]. Chawla et al [ 24 ] showed a high risk of bias with respect to the confounding variables (refer to Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In December 2019, novel evolved coronavirus called COVID-19 appeared for the first time [ 1 ]. This local epidemic has converted to a global pandemic, and more than two years later the repercussions stay unclear and dreadful [ 2 ]. At the start of 2022, the COVID-19 pandemic has been accountable for more than 100 million stated contaminations and 5 million deaths with dramatic social consequences [ 2 ].…”
Section: Introductionmentioning
confidence: 99%